2008
DOI: 10.1353/wp.0.0010
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Treaties and The Most-Favored-Nation Clause: The Myth of Trade Liberalization in the Nineteenth Century

Abstract: Textbook accounts of the Anglo-French trade agreement of 1860 argue that it heralded the beginning of a liberal trading order. This alleged success holds much interest from a modern policy point of view, for it rested on bilateral negotiations and most-favored-nation clauses. With the help of new data on international trade (the RICardo database), the authors provide empirical evidence and find that the treaty and subsequent network of MFN trade agreements coincided with the end of a period of unilateral liber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
18
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(22 citation statements)
references
References 29 publications
3
18
0
1
Order By: Relevance
“…Recent studies of the post-1945 world trade regime established through the General Agreement on Tariffs and Trade (GATT) and the World Trade Organization (WTO) have shown that the benefits for the average member -in terms of increased trade flows -might be insignificant (Rose 2004), while the core members who established the rules of the system and retained important bargaining power during its evolution gained significantly (Gowa andKim 2005, Westermeier 2008). Similar results have been obtained in recent studies of the first round of the Cobden-Chevalier network (Accominotti andFlandreau 2008, Lampe 2009a). …”
supporting
confidence: 90%
“…Recent studies of the post-1945 world trade regime established through the General Agreement on Tariffs and Trade (GATT) and the World Trade Organization (WTO) have shown that the benefits for the average member -in terms of increased trade flows -might be insignificant (Rose 2004), while the core members who established the rules of the system and retained important bargaining power during its evolution gained significantly (Gowa andKim 2005, Westermeier 2008). Similar results have been obtained in recent studies of the first round of the Cobden-Chevalier network (Accominotti andFlandreau 2008, Lampe 2009a). …”
supporting
confidence: 90%
“…Two potential answers for the absence of a more immediate reaction are: the liberalization was not very significant; or the adjustment costs of the shock were politically and economically tolerable. The former could be consistent with Flandreau and Accominotti (2008). The second view has not been well studied.…”
supporting
confidence: 72%
“…Naturally, this change is largest in cases of disappearance, averaging 552% for all coefficients and 2,201% for key coefficients. Note, however, that these averages are heavily influenced by two outliers in which both figures are more than two standard deviations above the mean (Accominotti and Flandreau 2008;Kurtz and Brooks 2008). Excluding these studies, the averages are 206% and 117%, respectively, similar to those in cases of strengthening (233% and 201%) and weakening (219% and 47%) but notably higher than those in cases of no change (135% and 74%).…”
mentioning
confidence: 76%